2007
DOI: 10.1080/01431160600993447
|View full text |Cite
|
Sign up to set email alerts
|

SRTM DEM accuracy assessment over vegetated areas in Norway

Abstract: Results from the Shuttle Radar Topography Mission (SRTM) are presented. The SRTM C-band and X-band digital elevation models (DEMs) are evaluated with regard to elevation accuracies over agricultural fields, forest areas and man-made features in Norway. High-resolution digital maps and satellite images are used as background data. In general, many terrain details can be observed in the SRTM elevation datasets. The elevation accuracy (90% confidence level) of the two SRTM systems is estimated to less than 6.5 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 6 publications
1
27
0
2
Order By: Relevance
“…The penetration depth and hence, volume scattering of the radar wave in vegetation is higher in C-compared to X-band. Weydahl et al [47] compared SRTM-X and SRTM-C band DEMs and demonstrated the relation between land cover type, radar wavelength and height errors. In general, the X-band height errors decreased from forest to lower canopies (e.g., agriculture).…”
Section: Accuracy Assessment Of Tandem-x Experimental Dem Productsmentioning
confidence: 99%
“…The penetration depth and hence, volume scattering of the radar wave in vegetation is higher in C-compared to X-band. Weydahl et al [47] compared SRTM-X and SRTM-C band DEMs and demonstrated the relation between land cover type, radar wavelength and height errors. In general, the X-band height errors decreased from forest to lower canopies (e.g., agriculture).…”
Section: Accuracy Assessment Of Tandem-x Experimental Dem Productsmentioning
confidence: 99%
“…The primary objective of TDM is to obtain a global Digital Elevation Model (DEM) with an absolute height accuracy better than 10 m and an equatorial spatial resolution of 12 m [8]. Because of the limited penetration of microwaves into the canopy, X-band interferograms over forests are characterized by an elevation offset which is dependent on forest canopy height and density [9]. This offset suggests exploiting TDM imagery to estimate tree height although a reference for the ground elevation is needed.…”
Section: Introductionmentioning
confidence: 99%
“…All three DEMs face some limitations for inundation modeling, since they are digital surface models (DSMs), which include vegetation and settlement structures in their height description (Gesch, 2009;Hofton et al, 2006;Hirt et al, 2010;Sun et al, 2003, Weydahl et al, 2007. This may lead to incorrect inundation extents and water depths.…”
Section: Creation Of Dtmsmentioning
confidence: 99%